Peruvian cities and the sustainable urban development law - Calderón Cockburn, Julio (2022)
The article discusses the problems and challenges of sustainable urban development (SDD) in Peruvian cities and focuses on the Sustainable Urban Development Law (SDL), number 31313, adopted in 2021. It considers urban sustainability, both in Peru and in the Latin American region, noting the effect of innovative policy and legislation, especially in Brazil and Colombia, as well as some of its difficulties and achievements. Secondly, it considers the LDUS in its political and social context, stressing its intention to regulate territorial development and urban planning by optimizing land use in “harmony with the common good and the general interest”. Finally, the conclusions and recommendations pose a number of challenges for urban sustainability in Peru.